Effectiveness of Bhabinkamtibmas Through the Online Binmas Application System Version 2 (Bos V2) in Reducing Theft With Aggregation in the Jurisdiction of Magetan Police - Sefriana Fajar; Jarot Muchtar; Timothy Ignatius Paskah Boske (Tanggon Kosala, 2024)
The high number of criminal offenses of theft with aggravation can be caused by the high expenditure that is not proportional to the income in Magetan Regency. The Binmas Online System Version 2 (BOS V2) application is the latest Baharkam breakthrough application that assists Bhabinkamtibmas personnel in maintaining public order. The purpose of this study is to determine the effectiveness of Bhabinkamtiba's performance and the use of the BOS V2 application by Bhabinkamtibmas in suppressing the number of thefts with aggravation (curat) in the Magetan Police jurisdiction. This research uses a qualitative approach with the type of field research. Primary data was collected using interviews, forum group discussions (FGD), and observation, while secondary data collection was sourced from document examination. Source triangulation was used to compare data from different sources. The research shows that the effectiveness of Bhabinkamtibmas performance and the use of BOS V2 have not suppressed the number of aggravated thefts in the Magetan Police jurisdiction. This is due to deficiencies in the application system and Bhabinkamtibmas, who are still having difficulty using this application.